Consumption of Sweet Foods and Tantrums: Can Biochemical Mechanisms Explain Emotional Dysregulation in Toddlers? - Ibnul Mubarok; Emeiliya Sufiani; Miftahul Jannah; Jamila Jamila; Dista Amalia; Aditya Rakhmawan (Journal of Literature Review, 2026)
Temper tantrums in toddlers are generally explained by psychological factors, while the role of biochemical mechanisms has not yet been extensively studied. This study aims to analyze the biochemical mechanisms underlying the relationship between the consumption of sugary foods and emotional dysregulation in toddlers. The study employed a qualitative descriptive approach through a literature review, analyzing scientific articles and reputable references on glucose metabolism, neurotransmitters, neurobiology, and emotional regulation. The analysis was conducted using content analysis to develop a conceptual synthesis of sucrose digestion, insulin regulation, adenosine triphosphate (ATP) production, dopamine and serotonin synthesis, and changes in gene expression through epigenetic mechanisms. The results of the study indicate that excessive sugar consumption has the potential to trigger fluctuations in blood glucose that disrupt neuronal energy homeostasis and neurotransmitter balance, thereby increasing susceptibility to emotional dysregulation. However, this relationship cannot yet be deemed causal, as it is also influenced by psychological and environmental factors. These findings underscore the importance of a multidisciplinary approach to understanding tantrums in toddlers and provide a foundation for future experimental research.